DILIrank: the largest reference drug list ranked by the risk for developing drug-induced liver injury in humans. Issue 4 (April 2016) - Chen, Minjun; Suzuki, Ayako; Thakkar, Shraddha; Yu, Ke; Hu, Chuchu; Tong, Weida
Highlights: DILIrank contains the largest number of drugs ( N  = 1036) ranked by their risk for causing DILI. The existing drug labeling-based DILI annotation was enhanced by weighing evidence of causality. Drugs were classified as verified v Most-, v Less-, v No-DILI-concern, leaving out terminology 'Ambiguous DILI-concern' drugs. DILIrank is invaluable for the development of predictive models using emerging technologies. High-throughput methods are powerful tools to develop predictive models for assessing drug-induced liver injury (DILI). However, the development of predictive models requires a drug reference list with an accurate annotation of DILI risk in humans. We previously developed a DILI annotation schema based on information curated from the US Food and Drug Administration (FDA)-approved drug labeling for 287 drugs. In this article, we refine the schema by weighing the evidence of causality (i.e., a verification process to evaluate a drug as the cause of DILI) and generate a data set that ranks the DILI risk (DILIrank) in humans for 1036 FDA-approved drugs, providing the largest annotated data set of such drugs in the public domain.